HISTOPATHOLOGICAL ANALYSIS OF THE PANCREAS IN WHITE RATS FOLLOWING ADMINISTRATION OF PURE MIMOSINE AND MIMOSINE IN LAMTORO LEAF POWDER - Berata, I Ketut; Kardena, I Made; Winaya, Ida Bagus Oka (Buletin Veteriner Udayana, 2025)
Mimosine in the lamtoro plant (Leucaena leucochepala) is a toxic or anti-nutritional ingredient which is reported to mainly cause hair loss in cattle. In addition, there is the possibility of many impacts on body tissue as a result of consuming feed ingredients containing mimosine. This study aims to determine the impact of mimosine in lamtoro leaf powder on histopathological changes in the pancreas of white rats (Rattus norvegicus). A total of 18 male Wistar strain white rats, 2 months old with a body weight of 250-300 g, were used in this study. Rats were randomly divided into 3 treatment groups, namely group P0 as a negative control (placebo), group P1 as a positive control given pure mimosine produced by Sigma at a dose of 5 mg/day, group P2 given mimosine from lamtoro leaf powder as a positive control at a dose of 50 mg/day Treatment was carried out every day for 14 days with a sonde. On day 15, all mice were euthanized and sacrificed for their pancreatic tissue. Next, the pancreas is processed to make histopathological preparations using the hematoxylin eosin (HE) staining method. Histopathological changes examined included lesions of congestion, bleeding and necrosis. Examination data is scored according to the distribution of lesions, namely normal criteria (score 0) if there are no lesions, mild criteria (score 1) if the lesion is focal, moderate criteria (score 2) if the lesion is multifocal and severe criteria (score 3) if the lesion is diffuse. The results of the examination showed that moderate levels of congestion lesions were found when mimosine was administered in lamtoro leaf powder. Mild necrotic lesions were found when mimosine was administered in lamtoro leaf powder, while moderate levels of necrotic lesions were found when standard mimosine was administered. It can be concluded that mimosine in lamtoro leaf powder can cause milder necrosis in the pancreas of white rats than standard mimosine administration. The flavonoid, tannin and protein components in lamtoro leaf powder can reduce the toxicity of mimosine. To reduce the effects of mimosine poisoning, it is best to limit the feeding of lamtoro leaves to livestock or before giving them to livestock, they should be given treatment to reduce the toxic effects.